Implementasi Media Digital Berbasis Quizizz Pada Mata Pelajaran Sejarah Kebudayaan Islam di MAN 2 Wonosobo - Fadila Khairunnisa; Pamungkas Stiya Mulyani; Faisal Kamal (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Over time, schools have adopted various learning technologies, one of which is the use of quiz-based media. Quizizz is an educational platform that presents learning in a gaming format, utilized as a tool for educating students. However, due to its proven benefits in education, especially in the subject of Islamic Cultural History, teachers at Madrasah Aliyah Negeri 2 Wonosobo continue to opt for its use in their teaching. The objectives of this research are: (1) To understand the Quizizz-based digital media in teaching Islamic Cultural History at MAN 2 Wonosobo, (2) To understand how teachers develop Quizizz-based digital media in the subject of Islamic cultural history at MAN 2 Wonosobo, (3) To understand the implications of Quizizz-based digital media in teaching Islamic cultural history at MAN 2 Wonosobo. The research method applied in this study is qualitative with a descriptive approach. This approach involves the use of observation methods, interviews, content analysis, and other data collection techniques. The study was conducted in the environment of Madrasah Aliyah Negeri 2 Wonosobo. After the data collection, data analysis was carried out, including the processes of reduction, presentation, and conclusion drawing. The findings of the study indicate that teachers have utilized the Quizizz digital platform in teaching Islamic Cultural History at MAN 2 Wonosobo, and students have responded positively. The study also illustrates that the utilization of Quizizz in teaching Islamic Cultural History at MAN 2 Wonosobo has proven to be quite successful, although there are some challenges that need to be addressed.